The role of Cholecalciferol in the Improvement of Insulin Resistance in Diabetic Mice Model - Elly Nurus Sakinah (Faculty of Medicine, University of Jember, 2017)
Insulin resistance is an important predictor of the incidence of diabetes mellitus. Vitamin D deficiency is one of the risk factors for insulin resistance, and there is a relationship between hypovitaminosis vitamin D with the prevalence of diabetes mellitus. Cholecalciferol is one form of vitamin D3. HOMA-IR levels are one of the parameters of insulin resistance. This study aims to prove that administration of cholecalciferol can improve insulin resistance conditions in diabetic mice model. This study used 20 mice divided into 5 groups negative control(STZ+propilen glycol), positive control (STZ+metformin), P1(STZ+cholealciferol 25ng), P2(STZ+cholealciferol 50ng), P3(STZ+cholealciferol 100ng). Mice given STZ dose 150mg / KgBB intraperitoneal to obtain hyperglycemia conditions. Administration of cholecalciferol for 14 days. The result obtained average HOMA-IR level after treatment is negative control(2,32), positive control (0,825), P1(0,975), P2(0,5), P3(0,3). The result obtained average HOMA-B level after treatment is negative control (2,76), positive control (11,92), P1 (18,4), P2(10,88), P3(35,35). The result of statistical analysis using Kruskall wallis test obtained p <0,005. The conclusion of this study is that administration of cholecalciferol may improve insulin resistance in diabetic model mice. Keyword : cholecalciferol, HOMA-IR, HOMA-B, streptozotocin